Recognizing the Dunning–Kruger Effect in the Early Stages of the Entrepreneurial Process - Ulčar, Lea; Marič, Miha (Improving Entrepreneurial Journey, 2025)
The chapter discusses the phenomenon of the Dunning-Kruger effect among the participants of the PONI LUR entrepreneurial training, which is conducted by RDA LUR in the Ljubljana Urban Region. The findings show that mentors often perceive an overestimation of their own entrepreneurial skills in participants, which can have a significant impact on the development of business ideas and business decision-making. Part of the research also included an in-depth interview with the program's internal mentor, who confirmed the presence of the Dunning-Kruger effect in the participants and described the existing approaches to address this challenge. Based on the analysed findings, proposals for improvements were formulated, including structured training of mentors, the introduction of reflective tools and the development of additional support after the training.